2010
DOI: 10.1016/j.aorn.2009.12.029
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Medical Waste

Abstract: Medical waste is a necessary by-product of any hospital environment; however, the majority of regulated medical waste is produced in the OR from the use of disposable surgical supplies (eg, drapes, gowns, basins, gloves, sponges). We conducted a concept comparison project in the ORs of two large medical centers in Bethesda, Maryland, and Washington, DC, to evaluate the effects of using reusable surgical basins, gowns, and table and Mayo stand covers in place of disposable products. Survey results indicated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
121
0
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(136 citation statements)
references
References 6 publications
0
121
0
7
Order By: Relevance
“…[20][21][22][23][24][25] However, many of these studies are outdated, and a 2010 life cycle analysis reported that reusable surgical linens showed a clear environmental and financial advantage over disposable linens. 26 Although further research on this topic is needed, hospitals, including ours, should consider transitioning to reusable surgical linens to reduce the volume of surgical waste produced.…”
Section: Recherchementioning
confidence: 99%
“…[20][21][22][23][24][25] However, many of these studies are outdated, and a 2010 life cycle analysis reported that reusable surgical linens showed a clear environmental and financial advantage over disposable linens. 26 Although further research on this topic is needed, hospitals, including ours, should consider transitioning to reusable surgical linens to reduce the volume of surgical waste produced.…”
Section: Recherchementioning
confidence: 99%
“…Biohazardous waste disposal from ORs accounts for nearly 20% of a hospital's environmental services budget. 6,7 Disposable medical devices also represent a significant OR expense. In 2009, Park and colleagues estimated that supply costs represent 58% of the total budget of an OR and this figure has been increasing.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental managers have been reported to contribute to organizations' legal [27] and profitable operations and represent the organization's sustainable aims to their staff. [25] An increasing number of studies are looking at environmental responsibility in hospital care by observing different areas, especially waste management [19,28,29] and sustainable activities in the operating theater. [20,23,30] In contrast, very few studies have looked at comprehensive environmental responsibility in hospital organizations [9] and have merely referred to structural skeletons that promote ecologically sustainable patient care.…”
Section: Introductionmentioning
confidence: 99%